Patients With Un-Displaced Or Displaced Intra Capsular Proximal Femur Fractures Do Not Represent A Different Patient Group And Have Similar Short And Long Term Mortality. Issue 4 (April 2022) - Ghosh, Soubhik; Thomas, Bijai; D'sa, Prashanth; John, Anoop; Amico, Giovanni Dall'; Williams, Rhodri; Bajada, Stefan
Highlights: Fracture displacement in intracapsular proximal femur fractures in elderly is not secondary to different pre-injury characteristics. Both groups have statistically similar short and long-term mortality rates irrespective of the treatment modality used. Long-term mortality (at 7-9 years) in geriatric proximal femur fracture cohort is significantly high at above 75%. Abstract: Background: Proximal femur fractures in geriatric patients are associated with substantial mortality. Management of intracapsular proximal femur fractures has been based on age, displacement, cognition, and pre-injury mobility. However, over the last decade, there has been a tendency to offer arthroplasty rather than internal fixation for these patients irrespective of displacement, to allow early mobilisation and negate the higher rate of reoperation due to failed internal fixation. There are no previous investigations analysing whether the severity of fracture displacement is related to different patient characteristics. Aim: This study examines whether patients sustaining undisplaced or displaced intracapsular proximal femur fractures represent different patient groups with different pre-injury characteristics and post-operative mortality, irrespective of treatment modality. Methods: A retrospective series of 329 consecutive patients over the age of 55 years who sustained intracapsular proximal femur fractures, who underwent surgical management at a district general hospital over a period of 2 years (2012-2013) were identified using the national hip fracture database. Demographics, American Society of Anaesthesiologist (ASA) grade, pre-injury outdoor mobility status, cognitive status, and admission serum investigations, fracture displacement, type of surgery, and mortality rates at short term (2 years) & long-term (7-9 years) were reviewed. Results: There were 109 male and 220 female patients with a minimum follow-up of 7 years. The mean age at surgery was 81.6 years (range 55-103 years). There were 63 (19.1%) undisplaced fractures (Garden 1 &2) and, 265 (80.5%) displaced fractures (Garden 3 & 4). The median survival in this cohort was 2.95 years (95% CI 2.3-3.6). Mortality rates were 77.4% (n=257) at long-term (7-9 years) follow-up. Admission patient characteristics showed no statistically significant difference between displaced and undisplaced fracture groups. This included ASA, pre-operative cognition, and mobility status. Fracture displacement was not an independent predictor of mortality at short or long term. Conclusion: In patients sustaining intracapsular proximal femur fractures, the degree of displacement is not a caveat for a different patient group. Fracture displacement is not predicted by the pre-injury level of function and does not predict short or long-term mortality.